2022
DOI: 10.3390/molecules27020563
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the Nutritional Value of PKC Using a Bacillus subtilis Derived Monocomponent β-Mannanase

Abstract: Palm kernel cake (PKC) is an abundant side stream that can only be added to non-ruminant feed in small concentrations due to its content of antinutritional factors, mainly galactomannan, which cannot be digested by non-ruminants. β-mannanases can be added to partially hydrolyze galactomannan to form mannose oligosaccharides, which are known to be prebiotic. We here investigate the action of a β-mannanase from B. subtilis on PKC by colorimetry, NMR and fluorescence microscopy. The amount of mannan oligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…PKC has a nonporous surface, whereas its fermented counterpart exhibits a looser shape and better microbial penetration and aeration (Saw et al, 2012). Osorio et al (2022) reported that using confocal immunofluorescence, showed a disruption in the structure of cellulose and galactomannan in the cell wall of PKC treated with β-mananase enzyme. This suggests that the use of β-mananase in PKC could convert mannan into mannan oligosaccharides, leading to the formation of prebiotic compounds.…”
Section: Content Of Fatty Acidsmentioning
confidence: 99%
“…PKC has a nonporous surface, whereas its fermented counterpart exhibits a looser shape and better microbial penetration and aeration (Saw et al, 2012). Osorio et al (2022) reported that using confocal immunofluorescence, showed a disruption in the structure of cellulose and galactomannan in the cell wall of PKC treated with β-mananase enzyme. This suggests that the use of β-mananase in PKC could convert mannan into mannan oligosaccharides, leading to the formation of prebiotic compounds.…”
Section: Content Of Fatty Acidsmentioning
confidence: 99%
“…Microscopy images of PKC cell wall showed an overlapping signal from mannan and cellulose (Gomez-Osorio et al, 2022). The close association between mannan and other polysaccharides may hinder the accessibility of mannan for further hydrolysis.…”
Section: Further Characterization Of F6004np110mentioning
confidence: 99%
“…are strong producers of β-mannanase (Abe et al, 1994;Chin, 2006;Pangsri et al, 2015;Gomez-Osorio et al, 2022). Several studies also reported that B. subtilis has high βmannanase activities and is capable of hydrolysing hemicellulose (Cheng et al, 2016) including those in PKC (Gomez-Osorio et al, 2022). Interestingly, Treatment 1 consisting of only three Bacilli spp.…”
Section: Analysis Of Reducing Sugarmentioning
confidence: 99%